The influence of a pressure medium on the accuracy of measurements in ultrasonic investigations of solids - J. KRÓLIKOWSKI; Z. WITCZAK (Archives of Acoustics)
The effects related to leaking of an ultrasonic wave from a solid sample through its end faces to a pressure medium were analysed in this paper. The influence of these effects on the results of measurements of the attenuation and the velocity of ultrasonic waves was experimentally investigated for several liquid and gaseous pressure media. The measurements were performed at a wave frequency of 10MHz and in a pressure range up to 1GPa.